A mitochondrial phosphatase required for cardiolipin biosynthesis: the PGP phosphatase Gep4 - Osman, Christof; Haag, Mathias; Wieland, Felix T.; Brügger, Britta; Langer, Thomas (The EMBO journal, 2010)
Cardiolipin (CL), a unique dimeric phosphoglycerolipid predominantly present in mitochondrial membranes, has pivotal functions for the cellular energy metabolism, mitochondrial dynamics and the initiation of apoptotic pathways. Perturbations in the mitochondrial CL metabolism cause cardiomyopathy in Barth syndrome. Here, we identify a novel phosphatase in the mitochondrial matrix space, Gep4, and demonstrate that it dephosphorylates phosphatidylglycerolphosphate to generate phosphatidylglycerol, an essential step during CL biosynthesis. Expression of a mitochondrially targeted variant of Escherichia coli phosphatase PgpA restores CL levels in Gep4-deficient cells, indicating functional conservation. A genetic epistasis analysis combined with the identification of intermediates of CL biosynthesis allowed us to integrate Gep4 in the CL-biosynthetic pathway and assign an essential function during early steps of CL synthesis to Tam41, which has previously been shown to be essential for the maintenance of normal CL levels. Our experiments provide the framework for the further dissection of mechanisms that are required for accumulation and maintenance of CL levels in mitochondria.
Gesehen am 19.06.2023